The Foreman/Supervisor's Handbook - Nance, H. W.; Carl Heyel, P. E.; SpringerLink (Online service) (Boston, MA : Springer US, 1984)
The Foreman/Supervisor's Handbook is offered as a com prehensive and authoritative text which presents the kind of prac tical information the foreman or supervisor needs in order to be effective on the job. It completely revises and updates The Foreman's Handbook, a work which, through four previous edi tions, has become the standard text in its field. The term "foreman/supervisor" in the title of the new edition was decided upon by the editors despite a reluctance to tamper with a well established name, in recognition of a change in usage which has come about over the years. "Supervisor" is now more generally used in industry for the first level of management and is espe cially appropriate since the emerging role of women in super visory (and higher) positions has rendered the earlier, gender specific term less properly descriptive. Moreover, although the orientation of the book is to manufacturing operations, the prin ciples and techniques discussed have wide application in office operations, where the term "supervisor" is the designation uni versally used. To retain continuity with the previous editions, the compromise term "foreman/supervisor" was adopted. As in previous editions, each chapter is written by an authority in the ~ubject covered. Each, morever, stands on its own feet, i. e. , it can be read as a separate article, independent of preceding or succeeding chapters.
Include index.
Keywords: Science (General).; Science, general; Science, general